group the 1st 2 terms and last 2 terms:
(Z63 -2z^2) + (9z-18)
factor out GCF:
z^2(z-2) + 9(z-2)
now factor the polynomial:
(z-2) (z^2+9)
Answer:
8.892
Step-by-step explanation:
15-6.108= 8.892
Answer:
m(u) = -0.25(u +2)² +1 or -0.25u² -u
Step-by-step explanation:
The equation is fairly easily written in vertex form, as the vertex point is on a grid line intersection at (-2, 1). The parabola opens downward, so the scale factor is negative.
The vertical change from the vertex is only a fraction of a unit when u differs from the vertex by 1. It is 1 unit when u differs from the vertex by 2, so the magnitude of the vertical scale factor is 1/2² = 1/4.
Our equation will be of the form ...
m(u) = (vertical scale factor)(u - (horizontal vertex location))² + (vertical vertex location)
For this graph, the equation is ...
m(u) = -0.25(u +2)² +1
or, simplifying, we get ...
m(u) = -0.25u² -u
Answer:
x = - ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
Step-by-step explanation:
To find f(g(x)) substitute x = g(x) into f(x), that is
f(g(x))
= f(x + 1)
= 2(x + 1)² ← expand using FOIL
= 2(x² + 2x + 1) ← distribute
= 2x² + 4x + 2
To find g(f(x)) substitute x = f(x) into g(x), that is
g(f(x))
= g(2x²)
= 2x² + 1
----------------------------------------------------------
Equating gives
2x² + 4x + 2 = 2x² + 1 ( subtract 2x² + 1 from both sides )
4x + 1 = 0 ( subtract 1 from both sides )
4x = - 1 ( divide both sides by 4 )
x = - ![\frac{1}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D)
If you do a check (plug in your answer to y) that would be your reason